ANALISIS KINERJA PERUSAHAAN BUMN SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Hendra Apriwarto; Heri Sasono (BADAN PENERBIT STIEPARI PRESS, 2022)
Companies are required to be able to generate profits for shareholders, including SOEs that must be able to provide dividends to the Government as shareholders. The purpose of this study is to see the relationship between the project undertaken with the company's. performance in terms of financial performance, from Financial Ratio Analysis. The population of this study is 9 (nine) state-owned construction companies and the research sample is 4 (four) state-owned construction companies. Research analysis using Financial Ratio Analysis is seen from Liquidity Ratios (CR, QR, CR), Solvency Ratios (ROA, ROE, GPM, OPM, NPM) and Profitability Ratios (DEA, DEA, LTDtER and OItLR). The conclusion of this study, seen from the total score the best (first order) is PT. Housing Development, the second place is PT. Wijaya Karya, third place is PT. Waskita Karya, the last order is PT. Adi Karya.